China and ASEAN-5 bilateral trade relationship - Siah, Kim Lan; Yusop, Zulkornain; Law, Siong Hook (Sunway University College, 2007)
This paper examines the China-ASEAN bilateral trade relationship, using the Gravity model where the per capita income difference is included in the specification for testing the hypothesis. The empirical results based on Bounds test proposed by Pesaran et al. (2001) reveal that the transportation cost and real GDP are statistically significant determinants of bilateral trade. The trade distance remains an important deterrent to China-ASEAN trade, and higher economy size of a country has positive and significant influence on bilateral trade flows. The significant positive sign of the per capita GDP difference (PGDPdiff) variable suggests that Linder Hypothesis does not hold for the entire region.